MOTIVASI PEMUSTAKA PADA LAYANAN REFERENSI DI BPAD PROPINSI RIAU 2011 - H, Rosman; Meriana, TM Tety (Jurnal Ilmu Budaya, 2012)
This writing deals with the motivation of users to reference service in BPAD Riau Province in 2011. It focuses on answering two question: 1) how users are motivated to use reference service, and 2) how far the users need the reference collections. Thus, motivation is the variable of the analysis and the users are the subvariable, while the indicator is viewed intrinsically and extrinsically. This analysis has 124 persons by applying qualitative descriptive analysis.